Thursday

March 26, 2015

March 26, 2015

Posted by **Cecilia** on Monday, April 5, 2010 at 3:42pm.

Ln(3x-4)-Ln(x+1)=Ln(2)

My solution:

Ln 3x-4/x+1 =Ln2

3x-4/x+1=2/1

2x+2=3x-4

2=x-4

6=x

- algebra -
**Reiny**, Monday, April 5, 2010 at 4:57pmyes you are correct, but you must put brackets when typing in this format.

On paper you probably extend the fraction bar over the (x+1) but the way you typed it, it would be understood as

3x - 4/x + 1 as 3 separate terms on the left side

check out this reply

http://www.jiskha.com/display.cgi?id=1270500607

**Answer this Question**

**Related Questions**

Calculus - Find the second derivative of the following function: y=log(base2)x/x...

Algebra II - Did I do this correctly? Use log laws to write the following ...

Algebra II-Please check - Did I do this correctly? Use log laws to write the ...

algebra 3-4 - im in a cal class but were reviewing algebra stuff now. and i have...

Algebra 1 - Solve each system graphically. Be sure to check your solution. If a ...

math - i have this question and im not sure how to do it i keep getting stuck ...

MATH - Find the solution of the given initial value problem. ty'+(t+1)y=t y(ln2...

Algebra 2 - Find the exact solution(s) of each system of equations? x^2+y^2=25 ...

ALGEBRA - I also have an answer for this one. Just need to be sure. Says to ...

Chemistry - Acetic acid (HOAc) is a weak acid with a Ka= 1.8 X 10^-5 and sodium ...